Предмет: Алгебра,
автор: S2rike
Найди значение выражения: (6c−10d)⋅(6c+10d)−36c2, если c=2 и d=0,01
Ответы
Автор ответа:
6
Решение с объяснением:
Раскроем скобки, получим
из (6c-10d)(6c+10d) - 36c^2 = 36c^2 - 100d^2 - 36c^2
Сократим 36c^2 - 36c^2 , получим
-100d^2
подставим d=0,01, то
-100*(0,01)^2 = -100* 0,0001 = -0,01
Быстрое решение:
(6c-10d)*(6c+10d)-36c^2 = 36c^2 - 100d^2 - 36c^2 = -100d^2 = -100*0,01*0,01= -0,01
Ответ: -0,01
Раскроем скобки, получим
из (6c-10d)(6c+10d) - 36c^2 = 36c^2 - 100d^2 - 36c^2
Сократим 36c^2 - 36c^2 , получим
-100d^2
подставим d=0,01, то
-100*(0,01)^2 = -100* 0,0001 = -0,01
Быстрое решение:
(6c-10d)*(6c+10d)-36c^2 = 36c^2 - 100d^2 - 36c^2 = -100d^2 = -100*0,01*0,01= -0,01
Ответ: -0,01
Похожие вопросы
Предмет: Математика,
автор: hytbjvxgm
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: aaazizaaa6496
Предмет: Математика,
автор: veklimova1977